ACADEMIC SUPERVISION BASED ON COACHING: A QUALITATIVE STUDY AT SD NEGERI SAMPANGAN 01 SEMARANG - Arry Widyanti; Endang Wuryandini; Muhammad Prayito (SOSIOEDUKASI, 2025)
This research investigates the implementation of academic supervision based on coaching at SD Negeri Sampangan 01 in Semarang, aiming to improve the quality of teaching and learning. The study employed a qualitative descriptive approach, focusing on the planning, execution, and follow-up of the coaching-based supervision process. The findings reveal that the planning phase involved a collaborative approach to identify teachers' developmental needs, set clear goals, and select appropriate coaching strategies. The implementation phase showed that coaching positively impacted teachers' confidence and teaching skills, encouraging reflective practice and innovative teaching methods. The follow-up phase emphasized continuous professional development through feedback and training, ensuring sustainable improvements in teaching quality. Despite its success, the study acknowledges some limitations, including its scope limited to a single school and the short-term duration of the research. Overall, coaching-based academic supervision significantly contributed to enhancing the teachers' professional growth and student learning outcomes.